2012
DOI: 10.4103/0301-4738.103779
|View full text |Cite
|
Sign up to set email alerts
|

Submacular hemorrhage: A study amongst Indian eyes

Abstract: Aim:To evaluate the management outcomes amongst various treatment modalities for submacular hemorrhage (SMH) in Indian subjects.Settings and Design:Retrospective, single-center study.Materials and Methods:Patients presenting with SMH between 1999 and 2006 were included. Treatment modalities included: vitrectomy with subretinal recombinant tissue plasminogen activator (r-tPA) assisted SMH evacuation (group 1, n = 14); pneumatic displacement with intravitreal r-tPA and gas (group 2, n = 25); and pneumatic displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…2,3,13,17,20 In our study, we found that good initial BCVA, small initial size of submacular hemorrhage and young age were statistically significant predictors for better visual prognosis. Other factors such as sex, hypertension, duration of hemorrhage, and presence of RPE detachment did not influence the outcome.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…2,3,13,17,20 In our study, we found that good initial BCVA, small initial size of submacular hemorrhage and young age were statistically significant predictors for better visual prognosis. Other factors such as sex, hypertension, duration of hemorrhage, and presence of RPE detachment did not influence the outcome.…”
Section: Discussionmentioning
confidence: 71%
“…5,7,8,17 PCV and massive submacular hemorrhage were risk factors for developing VH. 7,8 In our study, the only complication was VH at an incidence of 10%, which was lower than the 15% reported by Wu et al 8 There were no risk factors found to be associated with the occurrence of VH, which also did not affect the visual prognosis.…”
Section: Discussionmentioning
confidence: 98%
“… 4 Pneumatic displacement of large submacular hemorrhages with adjunctive intravitreal tissue plasminogen activator has been described and is best effective within less than 10 days from occurrence of symptoms. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Some recent reports [40][41][42] even suggest that intravitreal injection of tPA and gas without vitrectomy may be as effective in reducing blood volume as submacular injection of tPA with vitrectomy. Treatment with intravitreal tPA has also been reported to yield better functional and anatomic outcomes than pneumatic displacement alone [40].…”
Section: Discussionmentioning
confidence: 99%